Community-level effects of fragmentation of the afromontane grassland of the escarpment region of Mpumalanga, South Africa - Ferguson, J. Willem H. (University of Pretoria, 2013)
Dissertation (MSc (Zoology and Entomology))--University of Pretoria, 2005.